2022
DOI: 10.1161/circresaha.121.319822
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Resolution: Implications for Atherosclerosis

Abstract: Resolution is an active and highly coordinated process that occurs in response to inflammation to limit tissue damage and promote repair. When the resolution program fails, inflammation persists. It is now understood that failed resolution is a major underlying cause of many chronic inflammatory diseases. Here, we will review the major failures of resolution in atherosclerosis, including the imbalance of proinflammatory to pro-resolving mediator production, impaired clearance of dead cells, and functional chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 182 publications
0
43
0
2
Order By: Relevance
“…As early as the 19th century, pathologists Rokitansky and Virchow described the in ammatory characteristics of atherosclerotic plaques (Grebe et al, 2018). In recent years, multiple clinical studies have con rmed that the residual risk after traditional LDL-lowering therapy is mainly due to in ammation (Doran, 2022). According to the Canakinumab Anti-in ammatory Thrombosis Outcome Study (CANTOS), lowering low-grade systemic in ammation in CVD patients reduced the risk of acute cardiovascular events without affecting blood cholesterol levels (Ridker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As early as the 19th century, pathologists Rokitansky and Virchow described the in ammatory characteristics of atherosclerotic plaques (Grebe et al, 2018). In recent years, multiple clinical studies have con rmed that the residual risk after traditional LDL-lowering therapy is mainly due to in ammation (Doran, 2022). According to the Canakinumab Anti-in ammatory Thrombosis Outcome Study (CANTOS), lowering low-grade systemic in ammation in CVD patients reduced the risk of acute cardiovascular events without affecting blood cholesterol levels (Ridker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In many animal studies, SPMs have been shown to reduce plaque progression and some human studies also suggest a link between SPMs and ASCVD. A comprehensive review of the contribution of the inflammatory resolution, or lack thereof, to ASCVD was recently published by Doran [ 28 ]. SPMs have specific receptors that can promote inflammation or resolution depending upon the ligand binding to them.…”
Section: Inflammation In Cardiovascular Diseasementioning
confidence: 99%
“…Other emerging areas of research regarding how inflammation contributes to ASCVD include air and noise pollution, reduced and/or interrupted sleep, and other stressors [ 28 ]. These relationships open the door to considering how other methods of lifestyle modification could protect against ASCVD.…”
Section: Inflammation In Cardiovascular Diseasementioning
confidence: 99%
“…Unresolved inflammation has been proven to play a causal role in the onset of CVD [ 12 ]. As such, a clear understanding of these endogenous inflammatory processes is critical to pinpoint the cause behind the continuous nonresolution of cardiovascular inflammation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%